Taxonomic comments and an identification key to species for the Smooth-hound sharks genus Mustelus Link, 1790 (Chondrichthyes: Triakidae) from the Western South Atlantic. - Rosa, Marcos R.; Gadig, Otto Bismarck Fazzano [UNESP] (My University, 2010)
Five species of smooth-hound sharks genus Mustelus (Family Triakidae) are know in the western South Atlantic, as follows: Mustelus canis (Mitchell 1815); Mustelus fasciatus (Garman 1913); Mustelus higmani Springer & Lowe 1963; Mustelus norrisi Springer 1939; and Mustelus schmitti Springer 1939. In the present paper, new data on the anatomy, morphometrics and meristic characters are given. Taxonomic aspects and comparison between the species are discussed. Most general body morphologic measurements and proportions are useless as a tool for species identification, since many of them show remarkable intraspecific variations. Head proportions and structures related seem to be a more adequate procedure to identify the species of Mustelus. The labial folds proportions, internasal distance and orbit diameter were the most useful character to separate the western South Atlantic species. The buccopharingeal pattern of denticles as well as tooth counts not was useful to distinguish the Mustelus species from western South Atlantic adequately, due great intraspecific variation.